Effects of cold rolling on magnetic minor hysteresis loops of duplex stainless steels. Issue 6 (21st February 2017) - Kobayashi, Satoru; Murakami, Tatsuya; Narita, Yuki; Miura, Kodai; Kamada, Yasuhiro
Abstract: We have investigated scaling properties of magnetic minor hysteresis loops for duplex stainless steels with 60% ferrite and 40% austenitic phases, subjected to cold rolling up to 97% reduction. While the Steinmetz law, which is a scaling relation between maximum flux density and hysteresis loss and is generally valid for ferromagnetic steels, fails, that between remanent flux density and hysteresis loss exhibits a power law in the wide low and medium flux density regime, associated with a scaling exponent of . Further, the coefficient drops after rolling reduction of 10%, and then increases with reduction, whereas coercivity monotonically increases. Considering microstructural observations, the coefficient seems to also reflect morphology of the ferritic and austenitic phases in addition to the density of dislocations.